2013
DOI: 10.1021/ic400364x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Ligand Vibrations in FeNO, CoNO, and FeOO Porphyrin Adducts

Abstract: The gaseous ligands, CO, NO and O2 interact with the Fe ion in heme proteins largely via backbonding of Fe electrons to the π* orbitals of the XO (X = C, N, O) ligands. In these FeXO adducts, the Fe–X stretching frequency varies inversely with the X–O stretching frequency, since increased backbonding strengthens the Fe–X bond while weakening the X–O bond. Inverse frequency correlations have been observed for all three ligands, despite differing electronic and geometric structures, and despite variable composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 61 publications
3
18
0
Order By: Relevance
“…For more elaborate discussions of vibrational frequencies of CoP(NO) and structural parameters of both complexes, the reader is referred to the literature. 9,23 , formally assigned as the NO + complex, is slightly longer than the analogous distance in CoP(NO), formally assigned as the NO − complex. This holds true at least according to DFT:BP86 calculations, whereas the crystal structure data are less conclusive (the mentioned difference in bond distance is small and thus easily affected by crystal packing effects), although they also indicate that the (Co)N−O distance is about the same as the (Mn)N−O one, if not slightly shorter.…”
Section: ■ Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…For more elaborate discussions of vibrational frequencies of CoP(NO) and structural parameters of both complexes, the reader is referred to the literature. 9,23 , formally assigned as the NO + complex, is slightly longer than the analogous distance in CoP(NO), formally assigned as the NO − complex. This holds true at least according to DFT:BP86 calculations, whereas the crystal structure data are less conclusive (the mentioned difference in bond distance is small and thus easily affected by crystal packing effects), although they also indicate that the (Co)N−O distance is about the same as the (Mn)N−O one, if not slightly shorter.…”
Section: ■ Introductionmentioning
confidence: 80%
“…In fact, it is already a significant challenge to describe the complicated electronic structures of the resulting oxy-and nitrosyl-complexes, and to depict the metal−ligand bonding mechanism in strict chemical terms. 9,14−16 Another challenge for computational methods is to reproduce the metal−ligand bond dissociation energy with chemical accuracy. 11,12,17 In this regard, the recent studies of NO binding to Fe(II) and Fe(III) porphyrins revealed significant errors of common density functional theory (DFT) methods, some of which (hybrid functionals) tend to underestimate while others (pure functionals) tend to overestimate the Fe−NO bond energies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DFT modeling of 6-coordinate Fe(II)O 2 adducts with imidazole as axial ligand shows the same pattern as the 5-coordinate adducts [49] (Fig. 20).…”
Section: Fe(ii)o2 Adductsmentioning
confidence: 85%
“…Despite the longer Fe-O bonds, the νFeO frequencies shift to higher values, reflecting a shift in mode composition induced by the axial ligation [38, 49], as also seen for Fe(II)NO adducts ( Section 5.1).…”
Section: Fe(ii)o2 Adductsmentioning
confidence: 94%
See 1 more Smart Citation